2022
DOI: 10.1021/acsestwater.2c00005
|View full text |Cite
|
Sign up to set email alerts
|

Dilution and Pollution: Assessing the Impacts of Water Reuse and Flow Reduction on Water Quality in the Los Angeles River Basin

Abstract: Los Angeles (LA), California, USA is one of many population-dense, arid cities whose treated wastewater discharge comprises most of the river flow (up to 70% in the LA River). Like other arid cities, LA plans to improve water supply by reusing treated wastewater and diverting nonstorm stormdrain flows. This study quantifies the impact of these management actions on pollutant loads and concentrations in the LA River. Daily pollutant loads and concentrations for total suspended solids (TSS), total dissolved soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…On average, Tillman, Glendale, and Burbank WRPs typically discharge approximately 46 MGD (2.0 m 3 /s) of treated wastewater to the river (for water years 2011-2017), but they have plans to collectively reuse approximately 20% (California State Water Resources Control Board, 2017b;California State Water Resources Control Board, 2017a;City of Los Angeles Bureau of Sanitation, 2021). The flow, ecology, water quality, and temperature implications of these changes have been predicted by various other studies (Abdi et al, 2021;Stein et al, 2021a;Stein et al, 2021b;Abdi et al, 2022;Wolfand et al, 2022a;Wolfand et al, 2022b). Notably, previous work has found that indicator species may experience habitat degradation due to just a 4% decrease in wastewater discharge during the dry season (Wolfand et al, 2022b).…”
Section: Study Sitementioning
confidence: 80%
See 2 more Smart Citations
“…On average, Tillman, Glendale, and Burbank WRPs typically discharge approximately 46 MGD (2.0 m 3 /s) of treated wastewater to the river (for water years 2011-2017), but they have plans to collectively reuse approximately 20% (California State Water Resources Control Board, 2017b;California State Water Resources Control Board, 2017a;City of Los Angeles Bureau of Sanitation, 2021). The flow, ecology, water quality, and temperature implications of these changes have been predicted by various other studies (Abdi et al, 2021;Stein et al, 2021a;Stein et al, 2021b;Abdi et al, 2022;Wolfand et al, 2022a;Wolfand et al, 2022b). Notably, previous work has found that indicator species may experience habitat degradation due to just a 4% decrease in wastewater discharge during the dry season (Wolfand et al, 2022b).…”
Section: Study Sitementioning
confidence: 80%
“…Many rivers near highly populated areas are effluentdominated, where most river discharge is due to treated wastewater effluent, particularly during dry weather (Brooks et al, 2006). The water quality of this effluent can then dictate the water quality in the river (Wolfand et al, 2022a). Treated wastewater effluent can be of greater water quality than surface waters, as it is typically low in solids and metals (Wolfand et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effluent may have accounted for as much as 59% of streamflow at some locations in some years (Figure 4). Such predominance and flow-moderating effects of effluent in streamflow (Figure 4) are a common occurrence in urban streams in semiarid to arid regions [50,51].…”
Section: Streamflow and Municipal Water-use Patterns And Trendsmentioning
confidence: 95%
“…This indicator maximises resource access for human functions which can lead to undesirable consequences. This is demonstrated by the fact that maximising treated wastewater reuse at the cost of reduced discharge into a stream is known to cause a reduction of stream flow quantity and degradation of the stream water quality (Wolfand et al, 2022).…”
Section: Circularity Assessmentmentioning
confidence: 99%